LIFE SATISFACTION AND FACTORS AFFECTING SATISFACTION IN KAWAUCHI VILLAGE RESIDENTS AT 10 Y AFTER THE FUKUSHIMA DAIICHI NUCLEAR POWER PLANT ACCIDENT - Matsunaga, Hitomi; Orita, Makiko; Liu, Mengjie; Taira, Yasuyuki; Takamura, Noboru (Radiation protection dosimetry, 2022)
Abstract We assessed the life satisfaction and related factors, including the mental health state, of residents of Kawauchi village, Fukushima Prefecture. Among the 374 residents who responded, 237 (63.4%) were satisfied with their current life. Of all respondents, 275 (73.5%) had a sense of belonging to the Kawauchi village community and 158 (42.2%) thought that Kawauchi had recovered after the Fukushima Daiichi Nuclear Power Station (FDNPS) accident. Regression analysis revealed that post-traumatic stress disorder checklist-Specific score, sense of belonging to the Kawauchi village community, opinion that Kawauchi village had recovered, timing of return to Kawauchi <2 y and concern about consumption of mushrooms and wild plants from Kawauchi were independently associated with life satisfaction. Although 10 y have passed since the FDNPS accident, it is necessary to continue with risk communication, particularly for new residents of Kawauchi.